STUDENT ACCEPTANCE AND TEACHER ADAPTATION IN TAILORED EFL GAMIFICATION: THE ROLE OF LEARNER DIVERSITY - Eni Mahzumah; Nirwanto Maruf (Indonesian EFL Journal, 2026)
This study examined how learner diversity influences students’ acceptance of tailored gamification in English as a Foreign Language (EFL) classrooms and how both students and teachers perceive its implementation. Using a sequential mixed methods approach, the study first collected questionnaire data from 108 students, followed by semi structured interviews with 12 students and 2 teachers. Quantitative data were analyzed using descriptive statistics, Pearson correlation, multiple regression, and one way ANOVA, while qualitative data were analyzed thematically to explain the statistical results. The findings showed that learner diversity was positively related to students’ acceptance of gamified learning (r = 0.46, p < 0.01) and significantly predicted it (R² = 0.27, F(3,104) = 12.87, p < 0.001). Among the predictors, motivation had the strongest effect (β = 0.34, p < 0.001), followed by digital literacy (β = 0.28, p < 0.01) and proficiency level (β = 0.19, p < 0.05). Student acceptance also differed significantly across proficiency groups (F(2,105) = 6.45, p < 0.01). Qualitative findings highlighted three key themes: differentiated engagement driven by motivation, digital readiness as a condition for participation, and perceived fairness in gamified design. Teachers emphasized the need to adapt gamification to diverse learner needs through flexible and inclusive strategies. Overall, the study suggests that gamification is more likely to be effective when it is designed and implemented in ways that are responsive to learner diversity.